Bacterial Epigenomics: Coming of Age - Pedro H. Oliveira (American Society for Microbiology, 2021)
Epigenetic DNA methylation in bacteria has been traditionally studied in the context of antiparasitic defense and as part of the innate immune discrimination between self and nonself DNA. However, sequencing advances that allow genome-wide analysis of DNA methylation at the single-base resolution are nowadays expanding and have propelled a modern epigenomic revolution in our understanding of the extent, evolution, and physiological significance of methylation.